2021
DOI: 10.3390/ijms222212457
|View full text |Cite
|
Sign up to set email alerts
|

Microglia Reduce Herpes Simplex Virus 1 Lethality of Mice with Decreased T Cell and Interferon Responses in Brains

Abstract: Herpes simplex virus 1 (HSV-1) infects the majority of the human population and can induce encephalitis, which is the most common cause of sporadic, fatal encephalitis. An increase of microglia is detected in the brains of encephalitis patients. The issues regarding whether and how microglia protect the host and neurons from HSV-1 infection remain elusive. Using a murine infection model, we showed that HSV-1 infection on corneas increased the number of microglia to outnumber those of infiltrating leukocytes (m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 60 publications
3
9
0
Order By: Relevance
“…The study by Uyar et al showed that transient and incomplete depletion (6 day post infection) of microglial response decreased infiltration of monocytes/macrophages, neutrophils and T cells into the brain [ 45 ]. Similar results were obtained by Tsai et al in a study where microglia were depleted by the use of PLX 5622, an inhibitor of colony-stimulating factor 1 receptor (CSF1R), necessary for microglia survival, growth, and proliferation [ 46 ].…”
Section: Microglia In Viral Encephalitissupporting
confidence: 83%
See 4 more Smart Citations
“…The study by Uyar et al showed that transient and incomplete depletion (6 day post infection) of microglial response decreased infiltration of monocytes/macrophages, neutrophils and T cells into the brain [ 45 ]. Similar results were obtained by Tsai et al in a study where microglia were depleted by the use of PLX 5622, an inhibitor of colony-stimulating factor 1 receptor (CSF1R), necessary for microglia survival, growth, and proliferation [ 46 ].…”
Section: Microglia In Viral Encephalitissupporting
confidence: 83%
“…Depletion of microglia before and during infection augments brain viral titers by about 10- and 100-fold on days 6–7 p.i. and increases mortality rates of infected mice by 60 and 85%, respectively [ 46 ]. Lack of microglia activation is accompanied by increased infiltration of CD4 T cells, CD8 T cells, neutrophils, and increased production of IFN-β, and IFN-γ [ 45 , 46 ].…”
Section: Microglia In Viral Encephalitismentioning
confidence: 99%
See 3 more Smart Citations